Ambiguity as deliberate strategy: the 'de-politicized' discourse of national identity in the Taiwanese citizenship curriculum. Issue 3 (1st September 2016) - Hung, Cheng-Yu
Abstract : This article aims to investigate how the discourse on national identity is approached in the new Taiwanese citizenship curriculum. The differing opinions on Taiwan's relationship with China and the constant threat from this rising superpower have deterred the explicit promotion of either a Taiwanese or Chinese identity. The new curriculum follows a strategy of 'intentional ambiguity', where neither identity is mentioned. In this 'polysemous' form, the curriculum has been criticized for staying silent on the question of cultivating a national identity. However, the curriculum developers interviewed for this paper suggested that parents and pupils who examine the new curriculum can find support for whichever national identity they favor since it is designed in such an inclusive manner. They can then simultaneously reflect on the multiple, divergent or competing meanings behind the 'polysemous texts' and this 'hermeneutic' process of reasoning can then facilitate the choice of national identity with maximum acceptance.